2022
DOI: 10.1371/journal.pone.0265027
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Specific Demethylase 1 (LSD1) epigenetically controls osteoblast differentiation

Abstract: Epigenetic mechanisms regulate osteogenic lineage differentiation of mesenchymal stromal cells. Histone methylation is controlled by multiple lysine demethylases and is an important step in controlling local chromatin structure and gene expression. Here, we show that the lysine-specific histone demethylase Kdm1A/Lsd1 is abundantly expressed in osteoblasts and that its suppression impairs osteoblast differentiation and bone nodule formation in vitro. Although Lsd1 knockdown did not affect global H3K4 methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…In other complexes, such as the co-repressor of repressor element-1 silencing transcription factor (CoREST) complex, LSD1 targets H3K4me for demethylation ( 22 ). Different LSD1 complexes have been identified in different cell types and different contexts ( 25 27 ). Here we’ll briefly discuss the more commonly observed LSD1 complex composition, with a focus on those complexes likely to be important in sarcoma.…”
Section: Discovery Of Lsd1mentioning
confidence: 99%
See 2 more Smart Citations
“…In other complexes, such as the co-repressor of repressor element-1 silencing transcription factor (CoREST) complex, LSD1 targets H3K4me for demethylation ( 22 ). Different LSD1 complexes have been identified in different cell types and different contexts ( 25 27 ). Here we’ll briefly discuss the more commonly observed LSD1 complex composition, with a focus on those complexes likely to be important in sarcoma.…”
Section: Discovery Of Lsd1mentioning
confidence: 99%
“…In osteogenesis, the work that has been done demonstrates opposing functions of LSD1 in regulating bone formation. LSD1 is highly expressed in osteoblasts and is recruited to specific DNA motifs at osteogenic promoters to remove repressive histone methylation marks ( 25 ). LSD1 activity thus induces differentiation of osteoblasts to promote bone formation and in vitro knockdown of LSD1 in mouse mesenchymal cells impaired normal bone formation ( 25 ).…”
Section: Lsd1 In Mesenchymal Differentiation and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of LSD1 promotes osteoblast differentiation and bone formation in human mesenchymal stem cells (hMSCs) [ 28 ]. Interestingly, Petri et al reported that the suppression of the LSD1 activity inhibits osteoblast differentiation [ 29 ]. A recent study indicated that the deletion of LSD1 in female mice increases bone mass [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lysine (K)-specific demethylase 1 A (KDM1A, also refers to as LSD1) is a regulatory protein of methylation, which is one type of histone modification (Kim et al 2021). A previous publication reported that KDM1A used flavin adenine dinucleotide/dependent mechanism to demethylate H3K9me3 and regulated genes in MSCs (Rummukainen et al 2022). KDM1A was also shown to have a complex role in different stages of osteogenic differentiation (Wang et al 2018;Lv et al 2016).…”
Section: Introductionmentioning
confidence: 99%